Distributed dispatcher & scheduler with bandwidth constraint in edge computing - Low, Nicholas Zhi Wei (Nanyang Technological University, 2022)
In this report, we study the distributed dispatcher & scheduler with bandwidth constraint in edge computing. We will first image and create a cloud computing environment for a centralised solution. We then consider networking bandwidth constraints and a server’s computational resources before creating a centralised algorithm for dispatching and scheduling. Subsequently, we implement this algorithm in a simulation environment and confirm our understanding of the cloud computing concept and test the algorithm’s correctness. After which, the cloud computing environment will be viewed from a decentralised perspective where a decentralised solution can be formulated. A final decentralised solution will be created by modifying the above centralised solution to abide by the three key characteristics of a decentralised system, concurrency, loosely coupled and independent of failure.